Research on the Correlation between the Professionalism, Credibility of Internet Influencers and Consumers’ Purchase Intention - He, Chaoqun (Journal of Theory and Practice in Economics and Management, 2025)
This study aims to explore the impact of the professionalism and credibility of Internet influencers on consumers’ purchase intention. Through literature review, questionnaire surveys, and empirical analysis, it is found that both the professionalism and credibility of Internet influencers significantly affect consumers’ purchase intention. Internet influencers with stronger professionalism and higher credibility are more likely to stimulate consumers’ purchasing behavior. This research provides important theoretical support for enterprises in formulating Internet influencer marketing strategies.